Estudo da prática de escritores contemporâneos guineenses - Té, Júlio António Aponto [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The aim of this final essay is to study the writing practice of contemporary writers from Guinea Bissau, one of the countries of the former Portuguese colony, where the literature has developed very late, due to the lack of socio-cultural conditions for the development of the this practice. This happened because the country was delay was under colonial exploitation for a long time, under the command of the portuguese government. Among the elements that explain this situation is the presence of a restrictive and longcolonial education policy.The interest of this research consists in issues relating to the practice of writing and identity, It is an exploratory study which aims to gather information and reflect a) on discourses of contemporary Guinean writers about their writing practice and b) journalistic and academic discourses about the writing practice of these writers. The search of the corpus is made mainly on the Internet and the time frame set for the talks is collected from 1990 to 2010. The issues that guide the research are: 1) How is the writing practice of these writers ?, 2) What is the purpose of writing in this socio-historical context?, 3) What are the consequences of this practice for the production of the identity of these individuals? The results have revealed that: the practice of writing have a important role in the production of Guineansubject identity, because it has been related to the identity and political movements; the use of native languages and Creole in these practices, is indicative of the attempt to build in writing, an identity for the self who writes and for the other represented. This identity speaks to the cultural manifestations of the African people

O tema desta monografia é a prática da escrita de escritores contemporâneos da Guiné-Bissau, um dos países da antiga colônia portuguesa onde a literatura se desenvolveu muito tarde, devido ao atraso do aparecimento de condições sócio-culturais para o desenvolvimento dessa prática. Esse atraso deu-se através de exploração colonial que durou por um longo período sob o comando do governo português. Entre os elementos que explicam essa situação está presença de uma política educativa colonial restritiva e longa. O interesse desta pesquisa reside em questões relativas às práticas de escrita e identidade; é uma pesquisa exploratória que tem por finalidade levantar informações e refletir sobre discursos de escritores guineenses contemporâneos sobre sua prática de escrita e discursos jornalísticos e acadêmicos sobre a prática de escrita desses escritores. A busca do corpus é feita, principalmente, na internet e o recorte temporal definido para os discursos coletados é de 1990 a 2010. As questões que mobilizam a pesquisa são: 1) Como se dão as práticas de escrita desses escritores?; 2) Qual a função da escrita nesse contexto sócio-histórico?; 3) Quais as consequências dessa prática para a produção da identidade desses sujeitos? Os resultados permitem afirmar que: as práticas de escrita têm um papel importante na produção da identidade do sujeito guineense, pois têm sido relacionadas aos movimentos identitários e políticos; o uso das línguas nativas e do crioulo, nessas práticas, é indício da tentativa de construir, na escrita, uma identidade para o eu que redige e para o outro representado. Essa identidade dialoga com as manifestações culturais do povo africano
Keywords: Bakhtin, M. M. (Mikhail Mikhailovich), 1895-1975; Escrita; Literatura africana; Literatura africana (Portugues); Literatura guineense; Bakhtinian studies; Practice of writing; Media; Orality; African literature